PENGARUH PERSENTASE ZIRCONIA BALL TERHADAP VOLUME MILL JAR PADA PROSES PENGHALUSAN SERBUK KERAMIK ALUMINA DENGAN ALAT HORIZONTAL BALL MILL - Indra, Ade; Wigianto , Fadrian Wigianto; Perdana , Mastariyanto (Jurnal Rekayasa Mesin, 2024)
Research has been conducted on the effect of Zirconia Ball on the volume of Mill Jar in the process of smoothing Alumina ceramic powder with Horizontal Ball Mill tool. The research was conducted by adjusting the percentage variation of Zirconia Ball by 30%, 40%, 50%, 60%, 70%, and 80% of the Mill Jar capacity. Then the Particle Size Analyzer (PSA) test, observation of Alumina powder shape with Scanning Electron Microscope (SEM), and phase testing with X-Ray Diffraction (XRD) were conducted. From the PSA test results, it was found that the best pulverization results with the smallest results were found in the volume setting of 40% of the Mill Jar capacity carried out at a horizontal ball mill rotation of 150 rpm for 6 hours. These results were proven through PSA and SEM tests, and no Zirconia Ball contamination was found in the Alumina powder pulverization results.